Interplay Between KSHV and the Host DNA Damage Response - Ohsaki, Eriko; Ueda, Keiji (Frontiers in Cellular and Infection Microbiology, 2020)
Interactions between viruses and cellular factors are essential for viral replication or host defense. The DNA damage response (DDR) orchestrates a molecular network of cellular mechanisms that integrates cell cycle regulation and DNA repair or apoptosis. Numerous studies have revealed that the DDR is activated by virus infection, aberrant DNA structures generated by viral DNA replication, or the integration of retroviruses. Although the DDR is an essential function for maintaining the genomic integrity of cells, viruses may utilize this mechanism to build a convenient environment for themselves, and the resulting perturbation of the DDR has been shown to increase the risk of tumorigenesis. There have been many studies investigating the roles of the DDR in oncogenic viruses such as Epstein-Barr virus (EBV), human papillomavirus (HPV), hepatitis B virus (HBV), human T-cell leukemia virus type 1 (HTLV-1), and Kaposi’s sarcoma-associated herpesvirus (KSHV). This review summarizes current knowledge on the roles of DDR in the KSHV lifecycle.